Management Guidelines for Diabetic Patients With Hypertension - Weiqing Wang; Qin Wan; Suijun Wang; Guang Ning; Yufang Bi; Lianyong Liu; Yan Liu; Yu Liu; Xiaoying Li; Tingzhi Li; Xueyi Wu; Shengli Wu; et al. (Journal of Diabetes)
ABSTRACT Hypertension is one of the most common comorbidities associated with diabetes. The standardized diagnosis and treatment of hypertension in diabetic patients, along with achieving blood pressure targets, is of great significance for reducing long‐term complications, extending lifespan, and improving quality of life. Recent high‐quality multicenter large‐sample intervention studies have provided important evidence‐based grounds for setting blood pressure targets in diabetic patients. Therefore, based on a comprehensive summary of important domestic and international research literature, and in combination with clinical practice experience, this management guideline is now formulated.